Guess again - Donlea, Charlie (New York, NY : Kensington Publishing Corp., 2025)
"Ten years after teen volleyball star Callie Jones vanished without a trace, former detective Ethan Hall is pulled back to his haunted hometown to uncover long-buried secrets forcing him into a dangerous investigation with ties to his own dark past"--
Keywords: Missing persons -- Investigation -- Fiction; High school students -- Crimes against -- Fiction; Cold cases (Criminal investigation) -- Fiction; Detectives -- Fiction; Prisoners -- Fiction; Wisconsin -- Fiction; Psychological fiction; Thrillers (Fiction); Detective and mystery fiction; Novels